Spatial evolution characteristics of plasmapause surface wave during a geomagnetic storm on 16 July 2017 - Zhou,Y; He,F; Archer,MO; Zhang,X; Hao,YX; Yao,Z; Rong,Z; Wei,Y (Geophysical Research Letters, 2024)
Boundary dynamics are crucial for the transport of energy, mass, and momentum in geospace. The recently discovered plasmapause surface wave (PSW) plays a key role in the inner magnetosphere dynamics. However, a comprehensive investigation of spatial variations of the PSW remains absent. In this study, we elucidate the spatial characteristics of a PSW through observations from multiple spacecrafts in the magnetosphere. Following the initiation of the PSW, quasi-periodic injections of energetic ions, rather than electrons, are suggested to serve as energy source of the PSW. Based on the distinct wave and particle signatures, we categorize the PSW into four regions: seed region, growth region, stabilization region and decay region, spanning from nightside to afternoon plasmapause. These findings advance our understanding of universal boundary dynamics and contribute to a deeper comprehension of the pivotal roles of surface waves in the energy couplings within the magnetosphere-plasmasphere-ionosphere system.